Retour sur l’arc d’Orange (Vaucluse), son environnement et sa datation - Djamila Fellague (Gallia)
This article proposes a re-examination of the Arch of Orange based on ancient and recent data collected in urbanism and archeology. It is also the occasion for the author to share her thoughts concerning the scientific method that mostly relies on hypotheses. One of these idea concerning this famous monument of Orange assumes the existence of a first arch. If this construction existed we should wonder why it has been destroyed and we should also reconsider the inscription. Indeed, with this hypothesis the word restitutio could be understood as a reference to the destruction of this first arch. Associated to this hypothesis, the idea of a devasting flood will also be mentionned in the following lines but as this article is not an epigraphic study and because its purpose is not to provide any certainty, this thesis will only be briefly considered. In fact, the author wants to remind the reader of the uncertain nature of archeology even with such a well-known subject as the arch of Orange. For instance, if the idea of an arch originally dedicated to Germanicus then « given back » to Tiberius is now accepted as a fact, the author rejects this option and mentions that the Tiberian date for the monument has been lately debated. Actually, the arch of Orange – which is probably Augustan or Tiberian – demonstrates the difficult task in dating a monument on the basis of typology, which is yet nothing less than the founding principle of archaeology. Indeed, if the criteria selected are crucial their choice depends on the hypothesis defended.